The Effect of Inflationary Process of Government Revenue and Debt on Inflation in Indonesia: An Ardl Bounds Test Approach - Kafabih, An'im; Maskie, Gozalie; Hoetoro, Arif (Institute of Research and Community Service, University of Brawijaya, 2021)
The objective of this paper is to examine the cause of inflation based on fiscal policy perspective where government fiscal policy on government revenue and debt is such an inflationary process, meaning that if these two variables do not controlled properly, they will lead to higher level of inflation. Using annual data from 1972 to 2016 and ARDL bounds test approach to process these data, the result of co integration shows that government revenue and debt are simulaneously have long run relationship. This result is supported with the long run and short run relation for each independent variable individually. In the short run and long run, government revenue has positive impact on inflation with lower impact in the long-run compared to the short-run. Furthermore government debt also shows positive impact on inflation both in the long run and short run with the impact in the long run is higher rather that in the short run. As local governments depend heavily on national government on their fiscal resources, this study is also important to local governmentÂ because any decision of national government will affect to them.